Dual‐Fluorescent Nanoscale Coordination Polymers via a Mixed‐Ligand Synthetic Strategy and Their Use for Multichannel Imaging. Issue 2 (5th December 2017) - Nador, Fabiana; Wnuk, Karolina; García‐Pardo, Javier; Lorenzo, Julia; Solorzano, Rubén; Ruiz‐Molina, Daniel; Novio, Fernando
Abstract: Two rationally designed strategies for covalent bonding of fluorescent dyes in coordination polymer nanoparticles aiming to achieve bifunctional fluorescent nanostructures have been developed. The first strategy was based on the synthesis of the coordination polymers structured as nanoparticles by coordination of Co II ions to two different catechol ligands containing free functional chemical groups (dopamine and 3, 4‐dihydroxybenzaldehyde), and a bis(imidazole)‐based ligand (1, 4‐bis(imidazole‐1‐ylmethyl)benzene, bix). Subsequently, different dyes, namely fluorescein isothiocyanate (FITC), 1‐pyrenebutanoic acid hydrazide (PBH) or Alexa Fluor® 568 (A568), could be sequentially attached to the surface of the nanoparticles. The second strategy was focused on the prefunctionalization of catechol ligands with the corresponding dyes and, afterwards, the coordination with the metal ions in presence of bix. In vitro studies demonstrated the internalization of the bifunctional nanoparticles and the persistence of the fluorescent properties after cell uptake without dye leaching. Abstract : Dual‐fluorescent imaging probes : A series of dual‐fluorescent nanoscale coordination polymers with potential use in bioimaging has been prepared via a mixed‐ligand synthetic strategy using two approximations: a) a two‐step protocol where mixed‐ligand nanoparticles were post‐functionalized with different dyes, and b) a one‐step synthesis where the nanoparticles were formed using prefunctionalized ligands. In vitro studies were performed in order to stablish the viability of the resulting materials.